Multilingual dictionary of nuclear reactor physics and engineering - Anglart, Henryk (Boca Raton : CRC Press, 2021)
This multilingual dictionary explains, in simple and clear language, the most frequently used terms and expressions in the field of nuclear reactor physics and engineering, and provides translations of these terms from English into French, German, Swedish and Polish. This unique resource offers many advantages over the use of online translation tools, which are often incorrect when dealing with scientific and technical words. Instead, this dictionary has used a wide variety of peer-reviewed books and journal papers to ensure the highest accuracy and establish itself as a reliable and credible reference for the reader. It covers a broad range of exciting topics and the latest developments in the field, including reactor technology, reactor components and systems, reactor operation and control, reactor types, reactor physics, thermal engineering, reactor safety, radiation protection, nuclear fuel, nuclear chemistry, the safeguarding of nuclear materials and much more. This dictionary is kept on a technical level corresponding to masters-level and PhD studies of nuclear physics and engineering. It will provide the reader with a broad understanding of the necessary information that a researcher or nuclear physicist or engineer would need to possess; therefore, it will be an invaluable resource for students within these and related disciplines. Features: Contains over 1500 key terms from the field The first book to provide translations in five languages: English, French, German, Swedish and Polish Accessible to masters-level and PhD students in addition to early career researchers in nuclear reactor physics and engineering
OCLC-licensed vendor bibliographic record.
Keywords: Nuclear reactors -- Dictionaries -- Polyglot; Nuclear physics -- Dictionaries -- Polyglot; Nuclear engineering -- Dictionaries -- Polyglot; SCIENCE / Nuclear Physics; SCIENCE / Scientific Instruments; SCIENCE / Radiation